Pengaruh Debt to Equity Ratio, Earning per Share, Current Ratio, dan Firm Size terhadap Return Saham Perusahaan Farmasi di BEI Periode 2017-2019 - Nini Setyowati; Tri Utomo Prasetyo (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2021)
Abstract The purpose of this study is to examine and analyze the effect of debt to equity ratio (DER), earning per share (EPS), current ratio (CR), and firm size on stock returns in pharmaceutical companies in IDX for the 2017-2019 period. This research is a type of quantitative research using secondary data. The population in this study were all pharmaceutical companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The method used to select the sample is purposive sampling. The sample obtained using this method amounted to 5 (five) companies. The analytical method used is multiple linear regression. The results of this study, namely CR and Firm Size have a positive effect on stock returns. DER has a positive effect on stock returns which is not supporting the hypotheses, while EPS has no effect on stock returns.